Synthesis and characterization of PKFAD-Imperegnated chitosan as potential selective biosorbent for selective gold and copper sorption from aqueous solution / Mohamad Hanafi Hamzah and Chang Siu Hua - Hamzah, Mohamad Hanafi; Chang, Siu Hua (2020)
A new PKFAD-Imperegnated chitosan as a biosorbent was synthesized for the gold and copper sorption from the aqueous solutions. Chitosan is proven as one of the best adsorbents in order to recover or remove heavy metals in the aqueous solution. However, the problem with this chitosan is it has some disadvantages that restrict its application in the water treatment and purification. Chitosan show a poor acid resistance and low porosity and with these limitations, it clearly proves that raw chitosan is not suitable to be used as sorbent in adsorption process for metal recovery without further modification. Thus, the synthesize of PKFAD-impregnated chitosan can be used as a new biosorbent and it can solve the limitations of the existing chitosanbased biosorbent. In this reseach, the adsorption capacity of Au (ІІІ) and Cu (ІІ) from the aqueous solution on newly developed biosorbent PKFAD-impregnated chitosan beads were evaluated through batch experiments. The PKFAD-İmpregnated chitosan beads were synthesized into two ratio, which are chitosan: PKFAD (1:1) and chitosan: PKFAD (5:3). The sorption experiment is conducted by different value of Ph which is from ph 3, 3.5, 4, 4.5, 5 and 5.5. The sorbent used in the adsorption experiment is 0.1g. The characteristics of chitosan-based biosorbent were reviewed in order to predict the characterization PKFAD-Impregnated chitosan beads. The analysis including the Brunauer, Emmett and Teller (BET), scanning electron microscopy (SEM) and FTIR spectroscopy of chitosan-based biosorbent were reviewed in order to predict the characterization PKFAD-Impregnated chitosan beads. The maximum adsorption capacity of Au (ІІІ) obtained is 9.11 mg/g (98.65% ) which is in the ratio of chitosan : PKFAD (1:1). The maximum adsorption of Cu (ІІ) is 8.677 mg/g (87.65%) which is in the ratio of chitosan : PKFAD (1:1). The selectivity (Au (ІІІ) / Cu (ІІ)) is higher at a low value of pH for both ratio (1:1 & 5:3). The maximum selectivity (Au (ІІІ) / Cu (ІІ)) is 55.633 which is in the ratio of chitosan : PKFAD (1:1). The results show that the PKFAD-İmpregnated chitosan beads were efficient biosorbent for removal gold and copper in aqueous solutions.